Water-based binder preparation and full-color printing implementation of a self-developed 3D printer. Issue 3 (4th February 2021) - Li, Junchao; Yan, Ran; Yang, Yanan; Xie, Feng
Abstract : Purpose: The purpose of this study was to prepare water-based binders, which aimed to avoid printhead blockage and to improve dimensional accuracy of inkjet 3D printing (3DP) technology, and a feasible algorithm of full-color printing was realized. Design/methodology/approach: A self-developed color 3D printer was made by using a piezoelectric printhead of Epson Dx-5. Several water-based binders and corresponding gypsum composite powders were prepared, and the optimum binder-powder assembly was then determined through elementary adhesive testing and roller paving testing. Full-color printing was implemented based on halftoning algorithms that used different threshold matrices for different ink channels, and the performances of various algorithms were evaluated in terms of both subjective and objective indices. Findings: The optimum binder-powder assembly can solve the jamming problem of printhead and realize agreeable dimensional accuracy with the relative error less than 2.5% owing to the satisfying boundary diffusion control ability. And the determined halftone algorithm was verified to be agreeable for 3D color printing. Originality/value: The prepared approach of water-based binders and gypsum composite powders can be applied to similar 3DP systems even if different materials are introduced. And the used halftone algorithms provide feasible guidelines to the implementation of 3D full-color printing.